In Vitro Bronchorelaxant Effects of Capparis Spinosa Aqueous Extracts on Rat Trachea - Nadia BENZIDANE, Noureddine CHAREF, Imane KRACHE, Abderrahmane BAGHIANI and Lekhmici ARRAR (Journal of Applied Pharmaceutical Science, 2013)
Capparis spinosa (Capparidaceae) dicotyledons from the class of spermaphytes, is a shurb, enduring and woody plant, typically Mediterranean, largely used in folk medicine in the Mediterranean countries including Algeria. The aim of the present research is to assess the in vitro effects of aqueous extract of different parts of Capparis spinosa (leaves, fruits and seeds) on rat trachea in order to establish them as a real source for the isolation of bioactive compounds with potential use as anti-obstructive or anti-allergic agents. Rings of windpipes of rat Wistar were isolated, streamlined cut and suspended in organ bath containing 10 ml of Krebs physiological solution. The addition of Capparis spinosa extracts (0.1, 1 and 10 mg/ml) during the step of contraction by acetylcholine showed various effects on trachea. Incubation of the windpipe for 30 mn with extracts proves to be so efficient. The dose of 10 mg/ml showed a significant relaxant effect for fruits and seeds, and constrictor effect for the leaves. The results showed a potent relaxant effect of the fruit aqueous extract of Capparis spinosa, on rat trachea, with a dose dependant manner. However, the leaf aqueous extract has a contractive effect. A muscarinic receptor blockade/stimulation was suggested for caper/leaf extracts.
Keywords: Medicinal Plants, Capparis spinosa